2015
DOI: 10.1007/s00467-015-3257-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute kidney injury and chronic hypoxemia on fibroblast growth factor 23 levels in pediatric cardiac surgery patients

Abstract: Background FGF23 levels are elevated in cardiopulmonary bypass (CPB)-associated acute kidney injury (AKI); however, it is unknown how much of the circulating FGF23 is intact and bioactive. Hypoxia may induce FGF23 production, yet its impact in humans is unknown. Pediatric cardiac surgery patients have both a high incidence of CPB-associated AKI and a high prevalence of chronic hypoxemia. Methods We assessed the effects of hypoxemia and CPB-associated AKI on C-terminal FGF23 (cFGF23) and intact FGF23 (iFGF23)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
(56 reference statements)
3
23
0
Order By: Relevance
“…Interestingly, the area under the receiver operating characteristic curve, a measure of the predictive performance of an exposure, was higher for plasma cFGF23 (0.78) at the end of cardiopulmonary bypass compared with several urinary injury biomarkers, including neutrophil gelatinase-associated lipocalin (0.61), kidney injury molecule-1 (0.65), and n-acetyl-b-(D)-glucosaminidase (0.60). 99 Early increase of circulating FGF23 in patients with AKI after cardiac surgery also has been reported by other investigators, including in infants 111 and in children 100 (Table 2).…”
Section: Fgf23 Is An Early Prognostic Marker Of Incident Aki In Humanssupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the area under the receiver operating characteristic curve, a measure of the predictive performance of an exposure, was higher for plasma cFGF23 (0.78) at the end of cardiopulmonary bypass compared with several urinary injury biomarkers, including neutrophil gelatinase-associated lipocalin (0.61), kidney injury molecule-1 (0.65), and n-acetyl-b-(D)-glucosaminidase (0.60). 99 Early increase of circulating FGF23 in patients with AKI after cardiac surgery also has been reported by other investigators, including in infants 111 and in children 100 (Table 2).…”
Section: Fgf23 Is An Early Prognostic Marker Of Incident Aki In Humanssupporting
confidence: 83%
“…Similar findings were reported by Hanudel et al in a cohort of 32 children undergoing cardiac surgery. 100 These data are consistent with marked increases in both the production and cleavage of FGF23 in AKI. Similar findings have been reported in mice exposed to acute inflammatory stimuli, and in animal and human studies of iron-deficiency anemia.…”
Section: Fgf23 Is Increased In Human Akisupporting
confidence: 73%
“…Increase in cFGF23 levels is independent of changes in plasma PTH, phosphate and vitamin D metabolites ( Leaf et al, 2016 ). In pediatric and adult patients with AKI following cardiac surgery, there is a transient increase in plasma intact FGF23 (iFGF23) levels which subsequently normalize ( Hanudel et al, 2016 ; Leaf et al, 2016 ). Preoperative plasma cFGF23 levels in pediatric and adult patients undergoing cardiac surgery are associated with increased risk of AKI and post-operative mortality ( Speer et al, 2015 ; Hanudel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric and adult patients with AKI following cardiac surgery, there is a transient increase in plasma intact FGF23 (iFGF23) levels which subsequently normalize ( Hanudel et al, 2016 ; Leaf et al, 2016 ). Preoperative plasma cFGF23 levels in pediatric and adult patients undergoing cardiac surgery are associated with increased risk of AKI and post-operative mortality ( Speer et al, 2015 ; Hanudel et al, 2016 ). Although, pre- and post-operative cFGF23 levels serve as prognostic tools to predict post-operative AKI severity and complications ( Speer et al, 2015 ; Leaf et al, 2016 ), the mechanisms by which FGF23 levels increase in AKI are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…11,47,48 Clinical evidence confirmed that FGF-23 levels significantly increase in infants, children, adults, and older individuals suffering AKI. [49][50][51][52][53] FGF-23 is not only an early prognostic marker for cardiac surgeryassociated AKI and intensive care unit (ICU)-associated AKI but also serves as a prognostic marker for adverse outcomes in patients with established AKI. 11 Several studies have revealed the mechanisms underlying the upregulation of FGF-23 in AKI.…”
Section: Egf and The Egf Receptor In Akimentioning
confidence: 99%